2018
DOI: 10.1021/acssuschemeng.8b04073
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenized ionic liquid-metal oxide hybrids: enhanced catalytic activity in the liquid-phase Beckmann rearrangement

Abstract: We report the design of stable, ionic liquid-hybrids, covalently-anchored to the framework architectures of microporous and hierarchical solid supports. The ionic liquid moieties that are anchored to the framework facilitate enhanced mass-transport, and afford superior catalytic performance in the Beckmann rearrangement of cyclic oximes at low-temperatures. The ionic liquid-metal oxide (IL-MO) hybrids also play an important role in modifying the reaction 2 pathway and synergistic enhancements in catalytic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…In contrast, liquid-phase catalytic Beckmann rearrangement has become a topic of current interest because of its advantages such as mild reaction conditions, easy workup, and industrial practicability. As a consequence, different catalysts such as organic catalysts, , metal chlorides, and ionic liquids, have been investigated in this reaction. However, most of them suffer one or more shortcomings, such as expensive starting materials, harsh experimental conditions, complicated synthesis, and purification operations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, liquid-phase catalytic Beckmann rearrangement has become a topic of current interest because of its advantages such as mild reaction conditions, easy workup, and industrial practicability. As a consequence, different catalysts such as organic catalysts, , metal chlorides, and ionic liquids, have been investigated in this reaction. However, most of them suffer one or more shortcomings, such as expensive starting materials, harsh experimental conditions, complicated synthesis, and purification operations.…”
Section: Introductionmentioning
confidence: 99%
“…Annath et al [87] demonstrated Beckmann rearrangement of cyclic oximes to caprolactam in the presence of ionic liquid-metal oxide (IL-MO) hybrids. Ionic Liquid-metal oxide (IL-MO) hybrids also play an important role in modifying the reaction pathway and synergistic enhancements in catalytic properties are attributed to the increased hydrophobicity of the anchored, imidazolium-based ionic liquid.…”
Section: Ionic Liquidmentioning
confidence: 99%
“…Annath et al [87] . demonstrated Beckmann rearrangement of cyclic oximes to caprolactam in the presence of ionic liquid‐metal oxide (IL‐MO) hybrids.…”
Section: Various Attempts Have Been Undertaken To Perform the Beckman...mentioning
confidence: 99%
“…18 The large surface area and microporous structure make MOFs good candidates for heterogeneous catalysts with efficient mass delivery and high performance. With this method, Dong's group 19 and Raja and colleagues 20 pioneered the grafting of ILs on a MOF and a porous metal-oxide support for efficient CO 2 reduction and Beckmann rearrangement, respectively. Also, hierarchical pores on a MOF matrix were successfully manufactured recently, 21,22 with the original micropore (<2 nm) of a MOF and the artificial macropore (>50 nm), which are beneficial for the easy transport of a substrate having large van der Waals volume.…”
Section: Introductionmentioning
confidence: 99%